Mr. Science and Chairman Mao's cultural revolution science and technology in modern China - Wei, Chunjuan Nancy; Brock, Darryl E. (Lexington Books, 2013)
"Contributors approach the challenge of interpreting the science and technology of Chairman Mao's Cultural Revolution from different viewpoints, some as China-based scholars, others in the United States, and representing views of historians, political scientists, anthropologists, sociologists, literary scholars, and mathematicians. These scholars also represent a spectrum regarding their sense for the Cultural Revolution, ranging from skeptics who perceive little in the way of innovation or benefit from that period, to those who are agnostic, seeking evidence for S&T innovation, and others who lived through the Cultural Revolution, arguing the world has much yet to learn from socialist science"--